Effect of washing treatment on quality characteristics of burger made from spent laying duck meat - N F Md Fauzi; Nurul Huda; W Zzaman (2021)
Experiment was carried out to investigate the influence number of washing treatment (without, single and double washing) on the quality characteristics and acceptability of duck burger made from spent laying Khaki Campbell duck meat. The chemical composition of burger at different number of washing treatment was varied in terms of moisture content, fats and protein content. The number washing cycles treatment were found to increase moisture content and reduce fat and protein content significantly. Increase number of washing treatment showed significantly higher (p <0.05) lightness (L*), hardness, diameter shrinkage and cooking loss. As for sensory evaluation, there was no significantly difference (p >0.05) within the sample and control (chicken burger). The spent laying duck Khaki Campbell produced using different number of washing treatment may have a possible use as raw material in restructured meat products such as burger.